(untitled) - Strutt, Peter (Harlow, England, 2013)
English for international tourism is a three-level series designed to meet the English language needs of professionals working in the tourism industry and students of tourism in further education.
Keywords: Tourism,English language,English languages; Terminology,Problems, exercises, etc.,Textbooks for foreign speakers